Presenting a Model of Facilitating Factors in the Marketing Activities of the Iraq Wrestling Federation - Al-Shammari, Ameer Ayyed Abdalaimah; Esmaili, Mohammad Reza; Alturki, Alaa Hasan Ali; Zamani Nukaabadi, Alireza (Digital Transformation and Administration Innovation, 2025)
The purpose of this study was to present a model of facilitating factors in the marketing activities of the Iraq Wrestling Federation using the grounded theory approach and structural equation modeling (PLS-SEM). This research is applied in terms of purpose and employs a mixed-method (qualitative–quantitative) approach. In the qualitative phase, data were collected and analyzed through semi-structured interviews with 19 participants, including managers, experts, sports marketing specialists, and officials from the Iraq Wrestling Federation. Data analysis was conducted using open, axial, and selective coding within the framework of grounded theory, and components of the paradigmatic model (causal conditions, contextual conditions, intervening conditions, strategies, consequences, and central phenomenon) were extracted. In the quantitative phase, based on the qualitative findings, a researcher-made questionnaire was designed and distributed among 105 employees and managers of the federation. To reduce the number of variables in the model, a category compositing technique was employed. The collected data were analyzed using SmartPLS software. The modeling results indicated that the causal and structural paths of the model had a good fit, and statistically significant coefficients were obtained for all paths. The final model of the study demonstrates that institutionalizing a professional perspective on marketing, systematizing processes, and promoting organizational coherence play a central role in facilitating the marketing activities of the federation. Additionally, leveraging social, infrastructural, and institutional capacities alongside the removal of managerial and structural barriers is a prerequisite for realizing this framework. The findings of this study can assist sports policymakers in Iraq in designing effective and sustainable marketing structures.